EP1308 Minimally-invasive radical hysterectomy for early-stage cervical cancer: a no-touch, no-spill approach. (1st November 2019) - Beirne, JP; Chetty, N
Abstract : Introduction/Background: Several high profile studies, particularly Laparoscopic Approach to Cervical Cancer (LACC) trial, have reported MIRH was associated with worse prognosis than its open counterpart for the management of early-stage cervical cancer. Additional studies are needed to better understand the mechanisms explaining the worse survival associated with minimally-invasive surgery. However, it has been postulated that use of a uterine manipulator and an open colpotomy are responsible. We hypothesise that a no touch, no spill approach to MIRH will reverse this finding. This video presentation outlines a novel surgical technique that ensures cervical tumour does not encounter the surgical field during Minimally-Invasive Radical Hysterectomy (MIRH). Methodology: A case of a 38 year old female with FIGO IB1 Squamous Cell Carcinoma of the Cervix. Pre-operative staging MRI revealed a tumour size of 2 cm. A type III, nerve-sparing radical hysterectomy, bilateral salpingoophorectomy and pelvic node dissection (PND) was performed. A minimally-invasive approach was employed with assistance of a suprapubic Alexis GelPort© (Applied Medical). No uterine manipulator was used. An Endoloop© (Ethicon) suture to the adnexae aided manipulation. Routine PND was completed bilaterally. Routine ureteric tunnel dissection and bladder reflection was performed. Development of the recto-vaginal space and vaginal cuff was completed with hand-assistance. Infundibulopelvic and uterosacral ligaments were transected as standard. The GelPort was opened to allow cross-clamping of the vagina and excision of the specimen. Vaginal vault and all port sites were closed as standard. Results: The use of the Alexis GelPort© system allowed hand-assisted uterine manipulation, vaginal cuff development and an enclosed colpotomy technique. Conclusion: This novel approach to MIRH reduces the risk of intra-operative tumour spillage. Further refinement of the technique is in progress. However, further investigation of oncologic outcomes in larger prospective studies would be necessary to confirm our hypothesis. Disclosure: Nothing to disclose